2019
DOI: 10.1101/801902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term dynamics of aberrant neuronal activity in Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is associated with aberrant neuronal activity levels. How those activity alterations emerge and how stable they are over time in vivo, however, remains elusive to date. To address these questions we chronically recorded the activity from identified neurons in cortex of awake APPPS1 transgenic mice and their non-transgenic littermates over the course of 4 weeks by means of calcium imaging. Surprisingly, aberrant neuronal activity was very stable over time. Moreover, we identified a slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…Korzhova et al [94] recently identified a progressive increase in activity of intermediately active cells as the primary source of highly active neurons in the cortex of APP/PS1 mice, which was also observed in our model, supporting their hypothesis that network pathology may stem from stable aberrant activity of single cells.…”
Section: Discussionsupporting
confidence: 89%
“…Korzhova et al [94] recently identified a progressive increase in activity of intermediately active cells as the primary source of highly active neurons in the cortex of APP/PS1 mice, which was also observed in our model, supporting their hypothesis that network pathology may stem from stable aberrant activity of single cells.…”
Section: Discussionsupporting
confidence: 89%
“…Korzhova et al [92] recently identified a progressive increase in activity of intermediately active cells as the primary source of highly active neurons in the cortex of APP/PS1 mice, which was also observed in our model, supporting their hypothesis that network pathology may stem from stable aberrant activity of single cells.…”
Section: Excitatory and Inhibitory Synapse Loss May Distinctly Contribute To Network Dysregulationsupporting
confidence: 89%
“…2 ), which is in line with previous reports. 15 , 20 To characterize neuronal function, we quantified neuronal activity levels during stationary/quiescent epochs as well in response to whisking ( Fig. 1D ).…”
Section: Resultsmentioning
confidence: 99%